Zu einigen mittelalterlichen Amtsbezeichungen in der Toponymie Serbiens - Loma, Aleksandar (Linguistica (Ljubljana), 2015)
The paper deals with the place name Šepšin, designating a village in Serbia situated to the south of Belgrade, near the town of Mladenovac. According to the testimony of the Turkish 16th century tax registers, its modern form developed via Šemšin from the first recorded Šemčin (1528). On the assumption that the initial Š- derives from S- through the assimilation of the type šiče < siče 'hisses', the original form of the name may be reconstructed as *Sěmčijin, a possessive adjective derived from Old Serbian title (...). The underlying term, a hapax attested in the Banjska charter from 1316, is assumed to be the same as Old Church Slavic (...) 'prefect', which is probably a loanword from Proto-Bulgarian. In that case, the ě of the Old Serbian variant may be due to the influence of Common Slavic *(...) 'family'. In addition, another place name from the same region is reconsidered, Hrčin, today Vrčin, which displays a similar derivation. It has been variously interpreted so far, but by analogy with *Sěmčijin a proto-form *Hrtčijin seems rather probable, deriving from the unattested title *(...), which presumably designated an official at court charged with greyhounds (...) and generally with hunting. In both cases the masculine adjective in -in may have originally referred to potok 'creek' or dol 'valley' as a part of the feudal estate held by the official in question.
Keywords: krajevna imena; nazivi; Serbia; Serbie; Srbija; titres; toponymes